General Organization of Planning in Industry (Second edition)- Part II : Annual Planning/التنظيم العام للتخطيط في الصناعة (الطبعة الثانية) - الجزء الثاني: التخطيط السنوي - Sack, K.; Linsel, H. (INP, 2024)
paper